Weed Control and Crop Injury with Single or Sequential Herbicide Applications in Grain Sorghum - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2016)
The preemergence application of Dual II Magnum (S-metolachlor) improved the overall weed control compared to single postemergence treatments. Excessive rainfall after preemergence application compromised all treatments, producing abnormally low weed control.
Keywords: grain sorghum; weed control; crop injury; Dual II Magnum; S-metolchlor; Huskie; Pyrsulfotole; Bromoxynil; sorghum necrosis; Palmer amaranth; green foxtail